Tensile and morphological properties of carbon-coir fiber reinforced epoxy hybrid composites - Salahuddin Junus; Yayang Saif Izzudin; Aris Zainul Muttaqin; Danang Yudistiro; Mochamad Asrofi; Sumardi Sumardi; Puranggo Ganjar Widityo; Revvan Rifada Pradiza (Politeknik Negeri Lhokseumawe, 2025)
This study reports the tensile and morphological properties of carbon fiber-reinforced epoxy composites with the addition of coconut coir fiber. The composites were fabricated using the vacuum infusion method with coconut fiber weight fractions of 5%, 15%, and 25%. Tensile testing revealed that the highest tensile strength (70.92 MPa) was achieved at 15% fiber content, while 5% fiber content resulted in the lowest tensile strength (32.48 MPa). Scanning Electron Microscopy (SEM) and metallographic analyses showed variations in fiber-matrix bonding, with debonding and fiber pull-out observed at lower fiber content. The results suggest that optimal fiber-matrix bonding and fiber dispersion contribute to tensile strength enhancement, confirming the potential of coconut fiber-reinforced hybrid composites for structural applications